High rate of complications after operative fixation of open periprosthetic distal femur fractures - Yu Min Suh, MD; Robert Bardsley, BS; John Hwang, MD; Zachary Sirois, MD; Arun Aneja, MD; Jeffrey A. Foster, MD; J. R. Goetz, BS; Daria Kinchelow, BS; Chandler Sneed, BS; Shawn Dripchak, BS; Eric Swart, MD; John Garfi, MD; et al. (OTA International)
Abstract. Introduction:. The rate of open distal periprosthetic femur fractures is rising because of the aging population and increase in the frequency of total knee arthroplasties. Operative fixation of these complex injuries is often challenging. Multiple studies have evaluated outcomes of closed distal femur fractures, but outcomes after open injuries are unclear. Materials and Methods:. This is a multicenter retrospective case series of open periprosthetic distal femur fractures that were treated with open reduction and internal fixation at 7 institutions over a 10-year period. Standard demographic, injury, and operative data were collected. Charts were evaluated for complications including implant failure, deep infection, nonunion, malunion, and unplanned return to the operating room. Results:. Twenty-one patients were included with a mean age of 72.3 years. The mean postoperative follow-up was 23.8 months (4.2–105.5 months). Gustilo-Anderson fracture classification ranged as per the following: Type I (9), Type II (6), Type IIIA (5), and Type IIIB (1). Six patients were initially placed in an external fixator. Definitive fixation was either with an intramedullary nail (28.6%) or locked plating (71.4%). Eleven patients (52.4%) had at least 1 complication. All required return to the operating room at least once. Eight patients had a nonunion, 4 of which were septic and the other 4 aseptic. Two patients had a deep infection not involving a nonunion. Four patients were placed on lifelong suppressive antibiotics. The average time to union was 20.4 ± 14.1 months. Discussion:. This multicenter case series highlights the difficulty of treating open periprosthetic distal femur fractures as evidenced by the high complication rate (specifically nonunion and infection).